One‐pot preparation of multicolor polymeric nanoparticles with high brightness by single wavelength excitation. Issue 8 (1st October 2014) - Chen, Jian; Huang, Fuhua; Wang, Hong; Li, Ya; Liu, Shengli; Yi, Pinggui
ABSTRACT Fluorescent nanoparticles with multiplex distinct emission signatures and high brightness by a single wavelength excitation are substantially needed in multiplex bioassays and imaging. In this study, we synthesized fluorescent polymeric nanoparticles incorporated with three polymerizable organic dyes via a one‐pot miniemulsion. By altering the doping ratio of three tandem dyes, the nanoparticles display abundant multiple fluorescence such as blue, cyan, green, orange, pink, red etc., together with distinguishable emission signatures under a single wavelength excitation, which were arising from the effective fluorescence resonance energy transfer (FRET) between the three energy‐matched dyes. Meanwhile, a large Stokes shift (up to 250 nm) can be generated by taking place multiple FRET cascade mechanism between donor and acceptor fluorophores in nanoparticles, which also suggests broad applications in biological labeling and imaging. Moreover, these nanoparticles are uniform in size, highly bright, excellently photostable, and shown prominent longterm stability. Overall, the novel multicolor fluorescent polymeric nanoparticles augur well for their potential applications in multiplexed bioanalysis and emitting displays. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41492.